Reach out to one and you reach out to many: Social touch affects third‐party observers. (17th March 2014) - Schirmer, Annett; Reece, Christy; Zhao, Claris; Ng, Erik; Wu, Esther; Yen, Shih‐Cheng
<x xml:space="preserve">Abstract</x> Casual social touch influences emotional perceptions, attitudes, and behaviours of interaction partners. We asked whether these influences extend to third‐party observers. To this end, we developed the Social Touch Picture Set comprising line drawings of dyadic interactions, half of which entailed publicly acceptable casual touch and half of which served as no‐touch controls. In Experiment 1, participants provided basic image norms by rating how frequently they observed a displayed touch gesture in everyday life and how comfortable they were observing it. Results implied that some touch gestures were observed more frequently and with greater comfort than others (e.g., handshake vs. hug). All gestures, however, obtained rating scores suitable for inclusion in Experiments 2 and 3. In Experiment 2, participants rated perceived valence, arousal, and likeability of randomly presented touch and no‐touch images without being explicitly informed about touch. Image characters seemed more positive, aroused, and likeable when they touched as compared to when they did not touch. Image characters seemed more negative and aroused, but were equally likeable, when they received touch as compared to when there was no physical contact. In Experiment 3, participants passively viewed touch and no‐touch images while their eye movements were recorded. Differential gazing at touch as compared to no‐touch images emerged within the first 500 ms following image exposure and was largely restricted to the characters' upper body. Gazing at the touching body parts (e.g., hands) was minimal and largely unaffected by touch, suggesting that touch processing occurred outside the focus of visual attention. Together, these findings establish touch as an important visual cue and provide novel insights into how this cue modulates socio‐emotional processing in third‐party observers.